2021
DOI: 10.3390/v13030379
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Models for Studying SARS-CoV-2, the Etiological Agent Responsible for COVID-19 Pandemic

Abstract: The emergence and rapid worldwide spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has prompted the scientific community to rapidly develop in vitro and in vivo models that could be applied in COVID-19 research. In vitro models include two-dimensional (2D) cultures of immortalized cell lines or primary cells and three-dimensional (3D) cultures derived from lung, alveoli, bronchi, and other organs. Although cell-based systems are economic and allow strict control of experimental variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 136 publications
1
65
0
2
Order By: Relevance
“…Penetration routes can occur through damaged olfactory epithelium or via infected monocytes through compromised BBB later in the course of the disease. The neuropathology induced in this animal model makes it more suitable to further elaborate on neuropathogenesis of COVID-19 when compared to the Syrian hamster model which develop marked respiratory disease [33].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Penetration routes can occur through damaged olfactory epithelium or via infected monocytes through compromised BBB later in the course of the disease. The neuropathology induced in this animal model makes it more suitable to further elaborate on neuropathogenesis of COVID-19 when compared to the Syrian hamster model which develop marked respiratory disease [33].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…This result, together with the data obtained from other studies regarding the SARS-CoV-2 infection response in ferrets after injection of different viral loads, demonstrated that the virus could replicate in the upper respiratory tract of ferrets, showing a disease pattern similar to that of humans [ 65 ]. In addition, unlike mice and rats, ferrets exhibit the cough reflex; as coughing is the most frequently reported symptom in cases of SARS-CoV-2 infection, these animals represent promising models for this virus [ 68 ].…”
Section: Ferrets Models For Sars-cov-2mentioning
confidence: 99%
“…Similarly, in ferrets, the disease is relatively mild, and virus replication is mainly observed in the upper respiratory tract ( Shi et al, 2020 ). In addition, SARS-CoV-2 rapidly acquires spike protein mutations in ferrets as a result of critical species-specific differences in ACE2 receptor interactions ( Richard et al, 2020 ), showing the complexity of the response to viral infection in different animal hosts ( Leist et al, 2020 ; Rosa et al, 2021 ). All these models are costly and require specialised animal BSL-3 facilities.…”
Section: Introductionmentioning
confidence: 99%